The Role of Fingerprint System on Work Discipline at CV Bangun Jaya - Rochendi, Teddi (International Journal Labs, 2022)
Discipline is very important to achieve the goal. Especially in validity that is considered weak. This study aims to find out the influence of fingerprint absence on the work discipline of personnel at CV Bangun Jaya. The method used is the quantitative analysis method. The data was obtained by spreading questionnaires and using a sample saturated method, a sample of 20 respondents from a population of 20 employees. The techniques used are correlation coefficient test, determination coefficient test, and regression equation test. Based on the calculation of the correlation coefficient obtained the correlation coefficient of 0.953 shows that the level of relationship is very strong between fingerprint absence and work discipline. Fingerprint absence affected 90.8% of Work Disciplines, while the remaining 9.2% were affected by other factors not studied by the study. Based on the SPSS calculation table above, we can get an equation, namely: Y = 8,301 + 0.813X.